Making First Aid More Accessible During Mass-Casualty Incidents (International Journal of First Aid Education)
Because bystanders can play a vital role in delivering first aid prior to the arrival of emergency care, the Safety Region of IJsselland (www.in-prep.eu/srij/) together with the Netherlands Red Cross, developed a skill focused workshop called ‘Lifesaving Acts,” and then offered it freely to its citizens. Participants learn how to react in the critical moments following a mass casualty incident (MCI), while they are waiting emergency medical services (EMS) to arrive, through an engaging workshop that emphasizes building confidence to help over certification to use specialized equipment.